تأثير مدّة التجميد المنزلي في بعض الخواص الكيميائية والحسيّة لبعض أنواع أسماك الساحل السوري - عياش, علي أحمد; علي, علي أحمد (Latakia University Journal -Biological Sciences Series, 2013)
تمّ في هذا البحث اختيار خمسة من أنواع الأسماك الأكثر استهلاكاً في الساحل السوري المرلان، السرغوس، الغريبة صخري، المرمور، البوري شيلان. جمعت العيّنات من ساحة بيع السمك في اللاذقية وكانت بأوزان 150 - 200غ. نقلت العيّنات مبردة وبعد إزالة الحراشف والأحشاء الداخلية تمّ تجميدها لمدّة خمس ساعات على درجة حرارة-35°م ثمّ حفظت على درجة حرارة -18°م لمدة ستة أشهر. أجريت التحاليل الكيميائية على الأسماك قبل وبعد حفظها بالتجميد للمدد الآتية: أسبوع، شهر، شهران، أربعة أشهر، ستة أشهر، وشملت تقدير الرطوبة والبروتين والدهن والحموضة والآزوت الطيار ورقم البيروكسيد. كما أجريت أيضاً الاختبارات الحسية على الأسماك بعد قلي العينات المحفوظة بالتجميد للمدد المذكورة سابقاً، وشملت هذه الاختبارات الطعم والنكهة واللون والقوام ( تماسك اللحم وانتظام الشكل). أظهرت نتائج التحاليل الكيميائية انخفاض نسبة الرطوبة وارتفاع كلّ من الحموضة ونسبة الآزوت الطيار ورقم البيروكسيد في جميع الأنواع المدروسة مع تقدم مدة التجميد. أما الاختبارات الحسية فقد بيّنت تدهور الخواص الحسية مع تقدم مدة التجميد وبخاصة الطعم والنكهة وتماسك اللحم، وقد كان التغيير أكثر وضوحاً في نوعي سمك الغريبة والمرلان بحيث خفض ذلك من مدة احتفاظها بعوامل جودتها خلال التجميد إلى فترة أسبوع مقارنة بشهرين لبقية الأنواع الأربعة المدروسة. وربما يكون التدهور السريع في نوعي الغريبة والمرلان في أثناء الحفظ بالتجميد عائداً إلى ارتفاع محتواهما من المواد الدهنية أكثر من الأنواع الأخرى, وبخاصة خواص الطعم والنكهة وصلابة اللب. Five Species of the most widely consumed fish in the Syrian Coast (namely Merluccius merluccius, Diplodus sargus, Siganus luridus, Lithognathus mormyrus, and Chelon labrosus). were selected for this research. Samples were collected from the fish market in lattakia, with weight ranging between 150 and 200g. Samples were cleaned by removing scales and inner organs, freezed at -35°C for five hours and then stored at -18°C for a maximum period of six months. Chemical analysis of fish samples was carried out before and after freezing periods of one week, 1, 2, 4 and 6 months. Analysis included determination of moisture, proteins, lipids, acidity, volatile nitrogen, and peroxide value. Organoleptic evaluation was also performed on the control (fresh samples) and on the frozen samples after thawing and frying. The evaluation included taste, flavor, color, texture or meat consistency and form homogeneity. The results of the chemical analysis showed a decrease in moisture content and an increase in acidity, volatile nitrogen and peroxide values of all samples in proportion to the duration of storage. Organoleptic evaluation of the fried samples indicated deterioration of the studied quality characteristics, especially taste and flavor and meat consistency which was also proportional to the duration of storage. The deterioration was more obvious in the two species Gharibah and Merlan so that it limited the period of their storage to one week compared to two months for the other four species of fish. The fast deterioration in Gharibah and Merlan species during frozen storage may due to their higher content of lipids than the other species.